When cyberspace turns deadly: the significance of online harassment in intimate partner homicide - Cadwallader, Megan (Victimisation in the digital age, 2025)
This chapter considers the short and long-term effects of losing a loved one to intimate partner homicide (IPH), through means of online stalking and harassment, and explores what support is available to co-victims of IPH. Four semi-structured interviews were conducted with both male and female co-victims of IPH, whose loved ones had experienced a continuum of online-offline harm. Data collected was analysed using thematic analysis, where three primary themes emerged: (a) Proactive Help Seeking, (b) Inadequate Support, and (c) Neglect. The chapter contextualises these themes by drawing on the experiences of IPH co-victims and the support received. Finally, it considers the limitations of this empirical research and suggests specific recommendations for practice and future research.